Perbandingan Sensitivitas Serta Stabilitas MQ-4 dan MQ-5 Berbasis Arduino Untuk Deteksi Kebocoran Gas LPG - Yaaman Nazara; Gogor Christmass Setyawan; Agustinus Rudatyo Himamunanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
LPG gas leakage is a serious household safety threat in Indonesia, where 88.59% of households use LPG as their primary cooking fuel. Although colorless and faintly odorous at low concentrations, its flammable nature can cause explosions or fires if undetected. This research aims to compare MQ-4 and MQ-5 sensor performance in a single Arduino Uno-based gas leakage detection system. A quantitative experiment with direct comparison was conducted under identical conditions inside a sealed acrylic chamber measuring 16 × 12 × 10 cm, using LPG gas from a refillable lighter to simulate household leakage. Parameters measured include sensitivity, defined as the slope of the log(Rs/R₀) versus log(relative ppm) curve, and reading stability from the standard deviation of repeated measurements, where Rs is sensor resistance when exposed to gas and R₀ is resistance in clean air. All ppm values are relative estimates based on official sensor datasheets. Results show MQ-5 has higher sensitivity with a slope of 0.7914 compared to MQ-4 (0.6505), while MQ-4 is more stable with a log₁₀(Rs/R₀) standard deviation of 0.656 compared to MQ-5 (0.669). The system successfully detected all 30 leakage scenarios (100%) without false alarms, with a classification success rate of 99.0% per session. This research recommends MQ-5 for rapid early detection and MQ-4 for long-term monitoring requiring data consistency, thus both contribute as empirical evidence for a simple, accurate, and economical gas leakage detection solution.